Population Dynamics in Crișana and Banat During the Period 1990 – 2010 - Raboca, Horia Mihai; Raboca, Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The study analyses the population dynamics in Crișana and Banat territories, respectively from Bihor, Arad, Timiș and Caraș Severin counties. For this purpose, certain factors involved in this process were analyzed, respectively birth rate, mortality, the rate of natural population growth and the spatial migratory. As far as birth rate and mortality are concerned, these aspects had an oscillatory development, but adopting different directions of evolution, respectively a descending trend in the case of birth rate and an increase in the case of mortality. Due to this manner of manifestation result a negative rate of natural population growth in all the counties representing the main factor that caused the decline in population numbers in the territories mentioned. The analysis of the net migratory movement shows that migration growth has been positive on the whole interval where Bihor, Arad and Timis, alleviating to some extent the reduction in the population and negative values in a high proportion in Caras-Severin.